Factors Influencing Compliance With The Use Of Personal Protective Equipment By PT. Wiradijaya Workers In 2026 - Wahyu Hidayat; Usi Lanita; Andree Aulia Rahmat; David Kusmawan (International Journal of Health Engineering and Technology, 2026)
Occupational safety and health is an important aspect in industries with high work risks, including the oil and gas sector. Compliance with the use of personal protective equipment (PPE) is one of the main efforts to prevent occupational accidents and diseases. This study aims to identify factors associated with PPE use compliance among workers at PT. Wiradijaya in 2026. The study used an analytical observational design with a cross-sectional approach involving 90 workers selected by total sampling. Data were collected using validated and reliable questionnaires. The variables studied included knowledge, attitudes, supervision, motivation, and PPE use compliance. Data analysis was performed using the Chi-Square test. The results showed that most respondents had high compliance in PPE use (55.6%), good knowledge (53.3%), good attitudes (71.1%), good supervision (67.8%), and high work motivation (58.9%). Bivariate analysis indicated significant relationships between knowledge and PPE compliance (p=0.022), attitude and PPE compliance (p=0.016), supervision and PPE compliance (p=0.001), and work motivation and PPE compliance (p=0.037). Supervision was identified as the strongest factor associated with compliance. It can be concluded that individual and organizational factors influence workers' PPE compliance. Strengthening supervision, continuous safety training, and increasing worker motivation are recommended to improve PPE use compliance in the workplace.